Sumudu-Decomposition Method to Solve Generalized Hirota-Satsuma Coupled Kdv System - Azzo, Shrooq Mohammed; Manaa, Saad A. (Science Journal of University of Zakho, 2022)
In this work, we take Adomian Decomposition Method (ADM) and combine it with Sumudu Transform method (STM). This connection between the two methods is called Sumudu-Decomposition Method (SDM), then use it to solve generalized Hirota-Satsuma Coupled kdv (H-SC kdv) systems and also we applied the STM, to find the approximate solutions of system one. Then we compare the approximate solutions of the two way with exact solitary solutions. Clarifying the best way through tables and drawings, then discussing the reason for the changes taking place in the roads and which one is closest to the exact solution.